Efforts to Improve Non-Formal Education Through Memorization Programs at TPQ Al Jalalah, Tanjung Kertosono Village - Wathon, Aminul; Masrifatin, Yuni (Bisma : Bimbingan Swadaya Masyarakat, 2024)
The needs of the community are factual and actual in the service of the Qur'an Education Park (TPQ) as a center for religious character education. This article I made with the theme of increasing non-formal education through rote memorization at TPQ Al-Jalalah. and using the ABCD method Gondang Hamlet RT 11 RW 06 Tanjung Village, Kertosono Subdistrict, Nganjuk Regency. Researchers can conclude that children in TPQ Al Jalalah in terms of memorizing lack of interest or enthusiasm in memorizing. Memorizing learning at TPQ Al Jalalah is made as interesting as possible using techniques such as rote learning while playing memorization by relay (alternately) connecting verses, joint memorization techniques, individual private memorization techniques, memorization techniques, imitation and listening. memorization. And as a result, the children can perform optimally and well.